Environment, Archaeology, and History in Hittite Anatolia - Gorny, Ronald L. (The Biblical archaeologist, 1989)
The successful political integration of Anatolian settlements into the Hittite state seems to have been somewhat dependent on the way this civilization was able to respond to its physical setting.